Цитогенетическое обследование лиц разного возраста, выполненное с использованием дифференциального G-окрашивания метафазных хромосом - Талан, О.А.; Шеметун, Е.В.; Куринный, Д.А.; Пилинская, М.А. (Фактори експериментальної еволюції організмів, 2014)
Aim. To study of spontaneous frequency and spectrum of aberrations chromosomes in peripheral blood lymphocytes conditionally healthy volunteers of different age. Methods. Cultivation of peripheral blood lymphocytes received from ten conditionally healthy volunteers during 48 hours; G-banding staining of metaphase chromosome slides; scoring of slides under the microscope (cytogenetic analysis); identification of the full range of chromatid and chromosome aberration types. Results. Spontaneous frequencies of chromosome aberrations in peripheral blood lymphocytes of people in age from 10 to 100 years were determined using G-banding metaphase chromosome staining. The increase of chromosome aberrations frequency from adolescents to middle and elderly persons and lowering of chromosome mutagenesis in somatic cells of centenarians was shown. Conclusions. At the spontaneous mutational process of chromosomes aberrations frequency in peripheral blood lymphocytes were increased significantly with increasing age of the surveyed volunteers from 10 to 70 years old. For long-livers frequency of chromosome aberrations was lower than in the elderly one.